Molecular imaging of the extracellular matrix in the context of atherosclerosis - Reimann, Carolin; Brangsch, Julia; Colletini, Federico; Walter, Thula; Hamm, Bernd; Botnar, Rene M.; Makowski, Marcus R. (Advanced Drug Delivery Reviews, 2017)
This review summarizes the current status of molecular imaging of the extracellular matrix (ECM) in the context of atherosclerosis. Apart from cellular components, the ECM of the atherosclerotic plaque plays a relevant role during the initiation of atherosclerosis and its’ subsequent progression. Important structural and signaling components of the ECM include elastin, collagen and fibrin. However, the ECM not only plays a structural role in the arterial wall but also interacts with different cell types and has important biological signaling functions. Molecular imaging of the ECM has emerged as a new diagnostic tool to characterize biological aspects of atherosclerotic plaques, which cannot be characterized by current clinically established imaging techniques, such as X-ray angiography. Different types of molecular probes can be detected in vivo by imaging modalities such as magnetic resonance imaging (MRI), positron emission tomography (PET) and single photon emission computed tomography (SPECT). The modality specific signaling component of the molecular probe provides information about its spatial location and local concentration. The successful introduction of molecular imaging into clinical practice and guidelines could open new pathways for an earlier detection of disease processes and a better understanding of the disease state on a biological level. Quantitative in vivo molecular parameters could also contribute to the development and evaluation of novel cardiovascular therapeutic interventions and the assessment of response to treatment.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Atherosclerosis; Collagen; Elastin; Fibrin; Matrix metalloproteinases; Molecular imaging; MRI